2018
DOI: 10.5433/1679-0359.2018v39n6p2531
|View full text |Cite
|
Sign up to set email alerts
|

Immunocastration and its effects on carcass and meat traits of male pigs

Abstract: To compose the experiment, 160 male Topgen pigs - 80 surgically castrated (treatment 1) and 80 immunocastrated (treatment 2) - were randomly selected from a commercial swine farm at the moment of slaughter. Surgical castration was performed when the animals were seven days of age and immunocastration was performed by administering two doses (2 mL each) of immunocastration vaccine (analogue of GnRF linked to a carrier protein, development of anti-GnRF antibodies, 200 mg of a GnRF-protein conjugate/mL) when they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(21 reference statements)
2
1
0
Order By: Relevance
“…In the literature, the effect of the type of castration on color traits is not unanimous. Some reports [ 41 , 46 , 47 ] did not find differences between SCM and IM in any color trait but others [ 48 , 49 , 50 ] showed, as in the present work, that meat from IM presented lower L * value. Daza et al [ 36 ], Andreo et al [ 50 ] and Seiquer et al [ 42 ] observed that IM presented lower a * and values, and Škrlep et al [ 44 ] observed the opposite effect.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…In the literature, the effect of the type of castration on color traits is not unanimous. Some reports [ 41 , 46 , 47 ] did not find differences between SCM and IM in any color trait but others [ 48 , 49 , 50 ] showed, as in the present work, that meat from IM presented lower L * value. Daza et al [ 36 ], Andreo et al [ 50 ] and Seiquer et al [ 42 ] observed that IM presented lower a * and values, and Škrlep et al [ 44 ] observed the opposite effect.…”
Section: Resultssupporting
confidence: 64%
“…Some reports [ 41 , 46 , 47 ] did not find differences between SCM and IM in any color trait but others [ 48 , 49 , 50 ] showed, as in the present work, that meat from IM presented lower L * value. Daza et al [ 36 ], Andreo et al [ 50 ] and Seiquer et al [ 42 ] observed that IM presented lower a * and values, and Škrlep et al [ 44 ] observed the opposite effect. Different genetic types, pre-slaughter handling and conditions of data collection could contribute to pork color [ 51 ], generating differences unrelated to animal husbandry.…”
Section: Resultssupporting
confidence: 64%
“…In an experiment with immunocastrated pigs, Andreo et al (2018) affirmed that there is individual variation in the antibody titers generated by the vaccine among animals due to factors such as genetics, nutritional status, age and stress at the time of application, which explains the fact that in the present study animals have different responses to treatment. Gogić et al (2019) with swine, which found a reduction of 28.9 to 54.4% in the testis volumes and weights of immunocastrated animals compared to control animals.…”
Section: Resultsmentioning
confidence: 52%